The Discovery of Anxiousness Philosophy and Mysticism in Baroque Portugal - Serrado, Joana (Studien der Kulturwissenschaftlichen Gesellschaft, 2024)
Are anxiety or dread negative stages before freedom, a confrontation with humans' own mortality and finitude? Joana Serrado inaugurates anxiousness as a category of mystical knowledge in this innovative historical and philosophical study. Based on the life and mystical writings of Joana de Jesus, a Cistercian nun, intellectual disciple of Teresa of Avila, this study shows the cultural embeddedness of anxiousness: a feeling akin to the Portuguese term »saudade« (yearning, Sehnsucht). A mystical project that reshapes feminist principles of autonomy, agency and desire.